2018
DOI: 10.22270/ujpr.v3i1.r4
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Potency of Aqueous Extract of Harungana Madagascariensis Stem Bark Against Isoproterenol-Induced Myocardial Damage in Rats

Abstract: The present study was undertaken to evaluate the effects of Harungana madagascariensis on electrocardiographical, biochemical and histopathological changes in isoproterenol (ISO)-induced myocardial infarction in rats. Male Wistar albino rats were randomly divided and treated with the aqueous extract of Harungana madagascariensis stem bark (AEHM, 200 and 400 mg/kg per os), or normal saline or vitamin E for 7 days with concomitant administration of ISO (85 mg/kg, subcutaneously) on 8th and 9th days, at 24 h inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In contrast to oxidative chemicals, which are linked to raised airway tone and airway hyperresponsiveness, reduced glutathione, an antioxidant, lowers the airway tone [38]. On this basis, we can hypothesize that the antioxidant capacity of HMAE could contribute to the decreased effect observed on tracheal basal tone [22,39,40]. Interestingly, HMAE induced relaxant effects in tracheal rings precontracted with acetylcholine (Ach) or high K + (KCl).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to oxidative chemicals, which are linked to raised airway tone and airway hyperresponsiveness, reduced glutathione, an antioxidant, lowers the airway tone [38]. On this basis, we can hypothesize that the antioxidant capacity of HMAE could contribute to the decreased effect observed on tracheal basal tone [22,39,40]. Interestingly, HMAE induced relaxant effects in tracheal rings precontracted with acetylcholine (Ach) or high K + (KCl).…”
Section: Discussionmentioning
confidence: 99%
“…H. madagascariensis is very useful therapeutically. It has been reported to possess antispasmodic, antibacterial, antifungal, antiviral, and antihelminthic effects [15][16][17][18][19], antidiabetic, antioxidant, hypotensive and cardioprotective properties [20][21][22][23], anti-inflammatory and analgesic effects [24]. Additionally, we previously investigated the H. madagascariensis aqueous extract's acute and subacute toxicity and concluded that this extract did not show a significant toxicity effect in rodents [25].…”
Section: Introductionmentioning
confidence: 99%
“…Harungana madagascariensis is a component of Jubi Formula, a herbal preparation which was found to restore the packed cell volume (PCV), and haemoglobin (Hb) concentration in anaemia conditions and is a potential substitute for blood transfusion [12]. However, several scientific studies had reported that the ethanolic extract of H. madagascariensis possesses centrally-and peripherally-mediated analgesic properties [13], antioxidant and anti-modulatory effects [14] and hypotensive and cardioprotective effects [15,16].…”
Section: Introductionmentioning
confidence: 99%